Why the Cybermen Stomp: Sound in the New "Doctor Who." - Cranny-Francis, Anne (Mosaic: An Interdisciplinary Critical Journal, 2009)
This essay analyzes the meanings of the sound in the Cyberman double episode "Rise of the Cybermen" and "Age of Steel" of the television science fiction series "Doctor Who" by British Broadcasting Corp. (BBC). It explains that all sound in a text of the episodes contributes to its meanings. It also focuses and emphasizes the relationship between humans and technology.